NUMBER HEAD TOGETHER NHT TECHNIQUE IN IMPROVING STUDENTS’ READING SKILL ON HORTATORY EXPOSITION TEXT COOPERATIVE LEARNING METHOD - Rizka Indahyanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abstract: Number Head Together NHT Technique In Improving Students’ Reading Skill On Hortatory Exposition Text: Cooperative Learning Method. This research is aimed to find out whether or not the implementation of Number Head Together (NHT) technique improve the students’ reading skill on hortatory exposition text. During the researcher’s observation, it was found that students’ ability in reading was still low. The implementation of this research is starting by doing an observation and pre-test. Researcher then gave the treatment by teaching how to read and understand hortatory exposition text by using Number Head Together (NHT) Technique. Number Head Together (NHT) technique consists of four steps: numbering each student, asking questions, head together, and answering questions. The method of this research was quasi-experimental study. There were two group namely experimental group and control group. This research was conducted for six meeting. The last step of this research is doing a post-test and analyze the data taken from the test of hortatory exposition text.